2014
DOI: 10.5194/acp-14-1943-2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local surface albedo variability and ice crystal shape on passive remote sensing of thin cirrus

Abstract: Abstract. Airborne measurements of solar spectral radiance reflected by cirrus are performed with the HALO-Solar Radiation (HALO-SR) instrument onboard the High Altitude and Long Range Research Aircraft (HALO) in November 2010. The data are used to quantify the influence of surface albedo variability on the retrieval of cirrus optical thickness and crystal effective radius. The applied retrieval of cirrus optical properties is based on a standard two-wavelength approach utilizing measured and simulated reflect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…This gave us the opportunity to perform measurements in cloudy and in cloud-free air masses. HALO was equipped with a spectrometer system operated by University of Leipzig together with an instrument for measuring the actinic flux in cooperation with Forschungszentrum Jülich (HALO-SR) (Fricke et al, 2014), an automated high-volume air sampling system (MIRAH -Measurements of Stable Isotope Ratios in Atmospheric Trace Gases on HALO) of University of Wuppertal (Krebsbach et al, 2013), and an ion trap mass spectrometer of DLR (Roiger et al, 2011). Additionally, and in the focus of this paper, the DIAL system WALES (Wirth et al, 2009) was provided by DLR Institute of Atmospheric Physics (IPA).…”
Section: Introductionmentioning
confidence: 99%
“…This gave us the opportunity to perform measurements in cloudy and in cloud-free air masses. HALO was equipped with a spectrometer system operated by University of Leipzig together with an instrument for measuring the actinic flux in cooperation with Forschungszentrum Jülich (HALO-SR) (Fricke et al, 2014), an automated high-volume air sampling system (MIRAH -Measurements of Stable Isotope Ratios in Atmospheric Trace Gases on HALO) of University of Wuppertal (Krebsbach et al, 2013), and an ion trap mass spectrometer of DLR (Roiger et al, 2011). Additionally, and in the focus of this paper, the DIAL system WALES (Wirth et al, 2009) was provided by DLR Institute of Atmospheric Physics (IPA).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the surface albedo assumed in the forward simulations influences the uncertainty of the retrieved cloud properties (Rolland and Liou, 2001;Fricke et al, 2014;. For vertically homogenous clouds, these studies found uncertainties of up to 83 % and 62 % in the retrieved values of τ and r eff , respectively, when an inaccurate surface albedo is assumed in the forward simulation.…”
Section: Heterogeneity Of the Surface Albedomentioning
confidence: 92%
“…They showed that retrievals of clouds with τ < 0.5 are strongly influenced by variations in α. Based on RTS, Fricke et al (2014) concluded that I N measured in the nadir direction strongly depends on the underlying surface reflectivity and that uncertainties in assumed α may cause errors of up to 50 % in the retrieval of τ .…”
Section: Influence Of Surface Albedomentioning
confidence: 99%
“…This may introduce a bias in the retrieval of τ of up to 30 % when α is not accurately known or inhomogeneous (Fricke et al, 2014). Over dark ocean surfaces the radiance I reflected by the cirrus might be weak and can be on the same order of magnitude as Rayleigh scattering in the atmosphere.…”
mentioning
confidence: 99%
See 1 more Smart Citation